Low-cost, transportable hydrogen fueling station for early market adoption of fuel cell electric vehicles. (6th July 2015) - Richardson, Ian A.; Fisher, Jacob T.; Frome, Patrick E.; Smith, Ben O.; Guo, Shaotong; Chanda, Sayonsom; McFeely, Mikko S.; Miller, Austin M.; Leachman, Jacob W.
Abstract: Thousands of public hydrogen fueling stations are needed to support the early Fuel Cell Electric Vehicle (FCEV) market in the U.S.; as of July 2014 there were 12. Government agencies are the largest investors in the U.S. hydrogen fueling infrastructure and are developing stations that cost anywhere from $1.8–$5.9 million each. To attract private investors and decrease dependence on government funding, a low-cost, mobile hydrogen dispensing system must be developed. This paper describes a transportable 700 bar hydrogen fueling station that has been designed with an off-the-shelf component cost of $423, 000; less than 23% of the capital cost of current stations. The design utilizes liquid hydrogen storage and a novel cryogenic compression system which can be factory built for high volume, rapid production. These stations are contained in a standard 40 foot ISO shipping container to adapt to varying locational demand. The demand adjusted cost to sell hydrogen is estimated to be $9.62/kg. This paper presents the mechanical design and operation of the fueling station. This design won the grand prize for the 2014 Hydrogen Student Design competition and a complete report including an economic analysis and safety features is available elsewhere. Highlights: The design of a low-cost, transportable hydrogen fueling station to support fuel cell electric vehicles is proposed. This design utilizes liquid hydrogen storage and cryogenic compression which can be factory built for high volume production. These stations are contained in a standard 40 foot ISO shipping container to adapt to varying locational demand. The demand adjusted cost to dispense hydrogen is estimated to be $9.62/kg.